2022
DOI: 10.1007/s00784-022-04448-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive development in isolated Robin sequence treated with the Tuebingen palatal plate

Abstract: Objectives We aimed to determine the neurocognitive development of cleft palate patients with and without Robin sequence (RS). Materials and methods Children with isolated RS with cleft palate and children with cleft palate only (CPO) were contacted at the age of 5–6 years. All RS children had undergone initial polygraphic sleep study (PG) with a mixed-obstructive apnea index (MOAI) of ≥ 3/h and were consequently treated with the Tuebingen palatal plate. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…More recently, the German team from Tübingen evaluated the development of 22 children with RS who were 5.8 ± 0.6 years old, all receiving a pre‐epiglottic baton plate. The authors showed with the Wechsler Preschool and Primary Scale of Intelligence, First Edition, and the Kaufman Assessment Battery for Children that the children's development was within the normal range 16 . They recently confirmed their good results with the Wechsler Intelligence Scale for Children, Fifth Edition, in 21 children aged 9.7 years old 22 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…More recently, the German team from Tübingen evaluated the development of 22 children with RS who were 5.8 ± 0.6 years old, all receiving a pre‐epiglottic baton plate. The authors showed with the Wechsler Preschool and Primary Scale of Intelligence, First Edition, and the Kaufman Assessment Battery for Children that the children's development was within the normal range 16 . They recently confirmed their good results with the Wechsler Intelligence Scale for Children, Fifth Edition, in 21 children aged 9.7 years old 22 .…”
Section: Discussionmentioning
confidence: 90%
“…Tracheostomy remains the ultimate solution for all teams 9–12 . According to the studies that analysed the long‐term developmental outcome, the main point is that children with isolated RS have the potential for development within the normal range or very close to it 13–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation